The hostile hospital - Snicket, Lemony; Helquist, Brett (New York : HarperCollins, 2001)
Violet, Klaus, and Sunny disguise themselves as cheerful hospital volunteers after they are falsely accused of murder in order to find clues concerning their parents' deaths and are pursued by Count Olaf who is after their fortune.
Booklist.
Christian Library.
School Library Journal.
6.9
5-8
Keywords: Baudelaire, Klaus (Fictitious character) -- Fiction; Baudelaire, Sunny (Fictitious character) -- Fiction; Baudelaire, Violet (Fictitious character) -- Fiction; Brothers and sisters -- Fiction; Hospitals -- Fiction; Humorous stories; Orphans -- Fiction; Baudelaire, Klaus (Fictional character) -- Fiction; Baudelaire, Sunny (Fictional character) -- Fiction; Baudelaire, Violet (Fictional character) -- Fiction; Hospitals -- Fiction; Humorous fiction; Orphans -- Fiction; Siblings -- Fiction